Forced convection heat transfer, flow configuration and thermal performance in a square channel with modified v-shaped baffles - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2014)
The influences of modified V-shaped baffle in a square channel for heat transfer and thermal performance enhancement are presented numerically in three Dimensional (3D). The V-shaped baffles are modified in order to comfortable to installation in the square channel. The plates are used for clamping on both the upper and lower V-shaped baffles resulting the modified V-shaped baffle like orifice plate called "V-shaped orifice tubulators, VOT". The effects of Blockage Ratios (BR = 0.05-0.20), flow attack angles (α = 20°, 30° and 45°) and flow directions (V-Downstream and V-Upstream) with a single Pitch Ratio (PR = 1) are investigated for Reynolds number based on the hydraulic diameter of the square channel (Dh), Re = 100-2000. The fully developed periodic flow and heat transfer are applied for the computational domain. The SIMPLE algorithm and the finite volume method are used in the current study. The numerical results show that the use of VOT not only increasing heat transfer rate, but also rise up very enlarge pressure loss due to reducing the flow area of the cross sectional area. In addition, the maximum thermal enhancement factors are found around 2.4 and 2.5 for BR = 0.10, a = 30° at the highest Reynolds number of V-Downstream and V-Upstream, respectively. © 2014 Science Publications.
Keywords: Finite volume method; Laminar flow; Periodic concept; Thermal performance; V-shaped baffle